1996
DOI: 10.1016/0378-1097(95)00481-5
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into the use of SDS-PAGE of cell surface extracts and proteolytic activity to differentiate Prevotella nigrescens and Prevotella intermedia

Abstract: By comparison of the cell surface proteins derived from the outer membrane and fibrils from 14 Prevotella intermedia and 19 Prevotella nigrescens strains using SDS and analysed by SDS-PAGE, it was possible to distinguish the two species. A polypeptide of approx. 21 kDa distinguished P. intermedia strains, whereas two polypeptides of approx. 18 and 22 kDa could be used to identify P. nigrescens strains. Four other human oral black pigmented bacterial species (Porphyromonas gingivalis, Prevotella denticola, Prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…That most of the proteinase activity occurred cell‐associated is a common observation for periodontal microflora ( 6, 11). Most of the proteolytic activity in the rumen and the large intestine also resides in the bacterial fraction ( 15, 22).…”
Section: Discussionmentioning
confidence: 99%
“…That most of the proteinase activity occurred cell‐associated is a common observation for periodontal microflora ( 6, 11). Most of the proteolytic activity in the rumen and the large intestine also resides in the bacterial fraction ( 15, 22).…”
Section: Discussionmentioning
confidence: 99%
“…The genus Prevotella was separated from the Bacteroidiaceae in 1990 (23) and presently comprises diverse organisms that constitute the largest group of medically important gram-negative anaerobes. Cultured Prevotella organisms have been implicated in a wide range of infections, and some members of the genus express marked proteolytic activity and hemolysins (3)(4)(5)8). Typically, anaerobic culture significantly underestimates the abundance of Prevotella and other anaerobes at sites of infection.…”
mentioning
confidence: 99%
“…Previous studies have found no consistent differences between P. intermedia and P. nigrescens and observable phenotypic properties ( 4, 6–8, 10, 11, 19, 39). Nor did this study reveal any relationship between phenotypic characteristics and ribotype of either P. intermedia or P. nigrescens : there is no relationship between fibril type ( 7), coaggregating ability ( 8), adhesion to epithelial cells ( 10 and unpublished results) or hemagglutinating ability (unpublished results), and particular ribotypes.…”
Section: Discussionmentioning
confidence: 76%